Optimasi Larutan Penyerap Amina pada Pemurnian Biogas dari Kotoran Sapi - Elbi Zalita Pramadani Baros; Leila Kalsum; Rusdianasari (Postgraduate, University of Mataram, 2025)
The growing demand for energy and the depletion of fossil fuel resources have increased the urgency of finding renewable and sustainable energy sources. Biogas produced from cow manure through anaerobic digestion offers a promising option because it can turn agricultural waste into usable energy. However, raw biogas contains a high proportion of carbon dioxide (CO₂), which reduces its calorific value and must be removed to improve its quality. This research evaluates the effectiveness of four amine based absorbents, namely monoethanolamine (MEA), diethanolamine (DEA), triethanolamine (TEA) and methyldiethanolamine (MDEA), for purifying biogas in a packed absorption column. The column was filled with Pall rings to enhance gas and liquid contact and operated at room temperature (around 25 °C) and atmospheric pressure with a constant flow rate of biogas. Each amine solution was prepared at concentrations between 10% and 50%. The methane and carbon dioxide contents were measured before and after the purification process to assess removal efficiency. The findings indicate that MEA achieved the highest level of carbon dioxide removal, raising methane concentration from 58.3% to 78.2% at a 50% solution. DEA also showed good performance, although not as high as MEA, while TEA and MDEA produced lower removal efficiencies. These results demonstrate that amine based absorption can significantly improve the quality of biogas. In summary, MEA proved to be the most effective absorbent under the conditions tested, offering a practical and cost effective approach for small to medium scale biogas purification systems. These findings provide useful information for improving chemical absorption techniques to support wider use of renewable energy.